Darwin - Darwin, Charles, 1809-1882.; Goldie, Peter (San Francisco, CA : Lightbinders, 1936)
Includes complete texts and illustrations from Charles Darwin's works. Contains a timeline of events in Darwin's life, a biographical dictionary, and a bibliography of 1,500 primary and secondary sources. Natural sounds for some of the species discussed and a 7-minute video, "Down House Appeal," narrated by Sir David Attenborough are also included.
Darwin's works included on the disc: The origin of species (6th ed., 1872); The descent of man (1871); The voyage of the Beagle (1845); The expression of the emotions in man and animals (1872); The structure and distribution of coral reefs (1842); On the various contrivances by which British and foreign orchids are fertilised by insects (1862); The zoology of the voyage of the Beagle (1839-1842); short papers by Darwin, including "On the tendency of species to form varieties" (co-authored with A.R. Wallace, 1858), "On the formation of mould" (1838), "A biographical sketch of an infant" (1877), "Observations of proofs of recent elevation on the coast of Chile" (1837), and "Habits of ants" (1873); Darwin's 1,200-page barnacles monograph on the living and fossil Lepadidae and Balanidae, presented as one volume and containing a reference bibliography with over 2,300 entries.
Title from disc label.
"Created by Pete Goldie"--Container insert.
Previous ed.: The Darwin CD-ROM.
Sound recordings from the Cornell Laboratory of Ornithology.
System requirements (IBM PC or compatible): 80386SX or higher processor; 8 MB RAM and minimum 6 MB hard disk space; DOS 5.0 or higher; Windows 3.1 or later in enhanced mode with virtual memory; VGA monitor minimum (Super VGA with 256 colors and 800 x 600 resolution recommended); CD-ROM drive with MSCDEX 2.0 or higher.
System requirements (Macintosh): System 7 or higher; 8 MB of RAM (or 4 MB with virtual memory enabled); 9.5 MB of hard disk space; color display with 256 colors and 800 x 600 resolution; Macintosh compatible CD-ROM drive with Foreign File Access installed.
Keywords: Darwin, Charles, -- 1809-1882.; Darwin, Charles, -- 1809-1882 -- Bibliography; Evolution (Biology); Natural selection; Natural history -- South America; Zoology -- South America; Barnacles; Animal sounds -- South America; Barnacles -- Bibliography